484 Effects of Medicated and Control Feed on Weight Gain and Digestibility in Early Gestation Goats. (10th April 2018) - Bolton, A; Eier, J; Fischer, C; Williams, Z T; Williams, T L
Abstract: Coccidia has caused major un-thriftiness and substantial weight loss in susceptible small ruminant animals, such as goats, in both large- and small-scale farming. Intestinal damage due to coccidia infections reduce ability of intestines to absorb nutrients such as proteins. Protein within the diet is important in providing amino acids and nitrogen that are essential for weight gain. Weight gain is essential for gestating goats, not only for the health of the female but the health of the kid before and after birth. Decoquinate, a nontoxic quinolone anticoccidial treatment, can decrease these numbers of coccidia cases by developing a resistance towards the parasite. The current study, examined the effect of decoquinate inclusion in the diet on weight gain in mature, gestating, female goats. Twenty early gestation goats between the ages of 1 to 3 years were separated into two groups (n=10) to be fed a medicated (MED) or non-medicated (CON) diet to investigate weight gain. Medicated feed had decoquinate at 22.7 g/ton. Initial body weight of the goats ranged between 38.1 and 75.7 kg. Body weights were taken on 1 d, and 28 d after being on the feed trial, and every 7 d after, until 47 d was reached. The twenty cross-bred goats were housed in a single pen at the University of Findlay's Dr. C. Richard Beckett Animal Science Building. During feeding, goats were placed into individual feeding stalls, each goat received feed at 0.91 kg per 45.4 kg of body weight. All goats were fed twice daily at 0700 and 1800 hours. Overall, average weight gain for CON treatment was not different from the MED treatment, 17.0 lbs and 17.5 lbs respectively (P=0.773). With protein digestibility, no difference was seen in week one between medicated and non-medicated feed; 0.5540 and 0.5989 respectively. However, in weeks 2, 3, and 4, medicated feed had better protein digestibility with means; 0.5000 MED and 0.5989 CON, 0.4900 MED and 0.6011 CON, and 0.5750 MED and 0.6844 CON (P=0.013). Whether decoquinate is added in feeds or not, the effects on the weight gain of gestating goats would be similar to that of an equal nutritional feed. However, protein digestibility increased with inclusion of decoquinate in the diet, leading to a better overall gut health of gestating goats.